2005
DOI: 10.1111/j.1572-0241.2005.41057.x
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Bile Duct Stones in Suspected Biliary Pancreatitis: Comparison of MRCP, ERCP, and Intraductal US

Abstract: MRCP can be used to select patients with biliary pancreatitis who require ERCP. IDUS may be applied in the management of biliary pancreatitis if ERCP is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 30 publications
3
104
0
9
Order By: Relevance
“…Unfortunately, its performance in detecting CBD stones is disappointing, with a reported sensitivity of only 25% to 58% and a specificity of 68% to 91% [66]. The sensitivity of the CT scan for detecting CBD stones is about 40%, which is too low for it to be of clinical use [67]. However, MRCP is a very accurate method detecting CBD stones, with a reported sensitivity of 82% to 95%, a specificity of 97.5% to100%, a positive predictive value of 95% to100%, and a negative predictive value of 90% to 98% [33,[68][69][70][71][72][73].…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
“…Unfortunately, its performance in detecting CBD stones is disappointing, with a reported sensitivity of only 25% to 58% and a specificity of 68% to 91% [66]. The sensitivity of the CT scan for detecting CBD stones is about 40%, which is too low for it to be of clinical use [67]. However, MRCP is a very accurate method detecting CBD stones, with a reported sensitivity of 82% to 95%, a specificity of 97.5% to100%, a positive predictive value of 95% to100%, and a negative predictive value of 90% to 98% [33,[68][69][70][71][72][73].…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
“…4 Many studies agreed that MRCP are the procedure of choice for the diagnosis of hepatobiliary and pancreatic disorders. [12][13][14][15] Recently the use of rectal indomethacin or oral antacid to prevent PEP were mentioned in the literature and this is should be considered in our future procedures. 1,61,6,17 Upper gastrointestinal bleeding were the second most common complication 3.6% (16 cases), however hemorrhage is basically a complication related to sphincterotomy rather than diagnostic ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the accuracy of sonography and computed tomography scan, these imaging modalities are inferior to MRCP in diagnosis of choledocholithiasis [12][13][14]. Moon et al in their study on bile duct stones in suspected biliary pancreatitis revealed that overall agreement between MRCP and ERCP was 90.6% for detection of bile duct stones and concluded that MRCP can be used to select patients with biliary pancreatitis who require ERCP for intervention [18]. Mohan et al while evaluating the relative roles of MRCP and EUS in investigating CBD calculi "evidence based practice" methods concluded MRCP should be the first line of investigation of CBD calculi [19].…”
Section: Discussionmentioning
confidence: 99%